Soil Organic Carbon Estimation Through Participatory Approach in a Selective Village Common Forests in Chittagong Hill Tracts (Chittagong University Journal of Biological Sciences, 2024)
Abstract not availableThe Chittagong Univ. J. B. Sci. 9(1&2):167-178,2019